Prinsip Gereja yang Sinodal dalam Meningkatkan Kerukunan Antar Umat Beragama di Paroki MDKS Malang - Lazarus Satya Priyambada; Teresia Noiman Derung (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2025)
Inter-religious harmony is an essential foundation in maintaining social harmony in a pluralistic society, such as Indonesia. During the Jokowi presidency, there has been a significant increase in the interfaith harmony index, reflecting the growing awareness of pluralism and tolerance. Maria Di Angkat Ke Surga (MDKS) parish, located in Malang, actively contributes to creating harmony through various dialogue programs and social activities. This research aims to explore the implementation of the principles of the Synodal Church in the MDKS Parish in its efforts to enhance interfaith harmony. The research method applied is descriptive qualitative, with data collection techniques through observation, interview, and experience, involving key informants from the MDKS Parish priest. The results show that synodality or “Walking Together” is expressed in the celebration of the Eucharist and services to the people, as well as active participation in the Interfaith Harmony Forum (FKAUB). MDKS Parish also prioritizes the role of young people as key actors in building interfaith togetherness. In conclusion, MDKS Parish continues to implement the principles of synodality by building a comprehensive and inclusive community, so that it can be an example in creating authentic togetherness, respecting diversity and differences.